2023
DOI: 10.1039/d2nr06305k
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of nanosheet-assembled hollow copper–nickel phosphide spheres embedded in reduced graphene oxide texture for hybrid supercapacitors

Abstract: Thanks to their metalloid characteristics with high electrical conductivity, transition metal phosphides (TMPs) have demanded considerable research attention as prospective cathodes for hybrid supercapacitors. Unfortunately, they usually disclose low rate...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 52 publications
(22 citation statements)
references
References 81 publications
0
22
0
Order By: Relevance
“…The existing rGO skeleton around RCCS-ZSH8 not only served as an excellent conductive film to boost the conductivity of the sample but also acted as a protective layer to inhibit the aggregation of the particles. 36,37…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The existing rGO skeleton around RCCS-ZSH8 not only served as an excellent conductive film to boost the conductivity of the sample but also acted as a protective layer to inhibit the aggregation of the particles. 36,37…”
Section: Resultsmentioning
confidence: 99%
“…35 These drawbacks could be addressed using different approaches including, but not limited to (1) surface coating electrode material with appropriate active materials to enhance the redox reaction and improve the electrical conductivity, 10 (2) fabrication and structural design of electrode materials that could provide higher electroactive sites, 36,37 and (3) designing complex hollow nanoarchitectures encapsulated within conductive carbonaceous materials. 8,36,37…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…[24][25][26] Beneting from the enhanced conductivity, improved reactivity, and the synergy between several metal ions, mixed metal phosphides (MMPs) exhibit signicantly improved supercapacitive features compared with single MPs. 27,28 For example, Song et al synthesized Ni x Co 3−x P y nanostructures, which demonstrated a capacitance of 1969F g −1 at 1 A g −1 and excellent durability of 96% aer 10 000 cycles. 29 Also, Lei et al fabricated ZnNiCo-P nanoarrays with a good capacitance of 1111 C g −1 at 10 A g −1 and superior durability.…”
Section: Introductionmentioning
confidence: 99%